2011
DOI: 10.1530/eje-11-0476
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of diagnostic tests for GH deficiency in adults: a systematic review and meta-analysis

Abstract: Context: The diagnostic accuracy of tests used to diagnose GH deficiency (GHD) in adults is unclear. Objective: We conducted a systematic review and meta-analysis of studies that provided data on the available diagnostic tests. Data sources: We searched electronic databases (MEDLINE, EMBASE, Cochrane CENTRAL, Web of Sciences, and Scopus) through April 2011. Study selection: Review of reference lists and contact with experts identified additional candidate studies. Reviewers, working independently and in duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The median number of studies in the analyses was 13 (IQR 9–19) with a range from 4 to 118. Two review authors mentioned that a minimum of twenty homogeneous studies was required to perform a test [71,72]. …”
Section: Resultsmentioning
confidence: 99%
“…The median number of studies in the analyses was 13 (IQR 9–19) with a range from 4 to 118. Two review authors mentioned that a minimum of twenty homogeneous studies was required to perform a test [71,72]. …”
Section: Resultsmentioning
confidence: 99%
“…By reading the full texts of the included studies, we were able to identify how the different stages of liver fibrosis were reported using the Scheur, METAVIR, Ishak, and HAI systems. Since the histological definitions of liver fibrosis were similar [ 7 , 70 73 ], we unified the stages of liver fibrosis to mild fibrosis ( F ≥ 1), significant fibrosis ( F ≥ 2), advanced fibrosis ( F ≥ 3), and cirrhosis (F4). However, only two studies discussed mild fibrosis ( F ≥ 1), which made pooled analysis in this group impossible.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed significant number of false positive results in the control group. However, this study had few limitations; most importantly, the majority of patients involved in this study had mild TBI, second PD-GHRH stimulation is not a well-standardized test and is not used commonly for the diagnosis of GHD[ 81 ] and is not pertinent to confirm results acquired from ITT which is more sensitive. Third, GHRH-arginine test was used only for those patients who had contraindications to other tests though it has been more commonly used test and is also more widely available.…”
Section: Ncidence Of P Ituitary mentioning
confidence: 99%
“…Third, GHRH-arginine test was used only for those patients who had contraindications to other tests though it has been more commonly used test and is also more widely available. [ 81 ] Recently, a systematic review has been published in which authors compared either the prevalence of abnormal endocrine tests was higher in TBI patients as compared to controls or not and included only those studies that applied at least one endocrine test in a matched control group. [ 5 ] They found that pooled prevalence of GHD was 7.7% and 1.4% in patients and controls respectively ( P < 0.001) according to the results obtained from ITT using local cut-offs values by Klose et al .…”
Section: Ncidence Of P Ituitary mentioning
confidence: 99%